Comparative analysis of the school program (and curriculum) teaching sociology in Croatian and French secondary schools - Mikeš, Maja (Array, 2013)
The analysis of curriculum and objectives of the curriculum compares the basic starting point of teaching sociology in French and Croatian general education system and emphasize that sociology, as a scientific discipline, has a completely different status. In Croatian gymnasium sociology is taught within the school subject "Sociology", which is a separate subject, while in the French lycée it is taught as a multidisciplinary subject called „Scienceséconomiques et sociales". While the main goal in Croatia is acquisition of basic theoretical approaches, concepts and research methods of sociology, in France, the emphasis is on the student's insight into the complexity of the social world and the ability to study and clarify the same from different perspectives. It follows that, in France, the objectives of the teaching process are defined as outcomes, while the Croatian curriculum focuses on the content of the teaching process. The difference is also in the scope as opposed to "Sociology", which is just one of the subjects that are taught for one school year, subject "Scienceséconomiques et sociales" is the main school subject of students who have chosen the economic and social direction in the Lyceum. The conclusion is that the general objectives are still largely similar because both systems seek to educate citizens of modern democratic society. The work elaborates that the Croatian curriculum, in many aspects, compared to the French is simply outdated.